COMPARISON OF THE EFFECTIVENESS ONLINE AND OFFLINE REGISTRATION SYSTEM ON PATIENT WAITING TIME IN PRIMARY HEALTH CARE SEMARANG USING QUEUING THEORY - Evina Widianawati; Faik Agiwahyuanto; Trianni Trianni; Adelia Ayu Sabrina; Dimas Angga Febian (Kresnamedia Publisher, 2021)
The online registration system at Semarang's Primary Health Care has been implemented in 2018, but online registration users are still small. The purpose of this study was to compare the effectiveness of online and offline registration at waiting times using variables in queuing theory. Research at 3 health centers in the city of Semarang. By observing the time of arrival and time of admission to the patient's clinic then the patient is also given a registration service satisfaction questionnaire sheet. The data were processed using queuing theory variables as well as descriptive and inferential statistical analysis. The number of online registrants is only 12% while 88% registered offline. The total number of online registrant patient arrivals per hour is 0.85 patients and offline registrants are 6.38 patients per hour where many patients arrive at the first 105 minutes to open the puskesmas. The utility of the online registrant registration server is 7%, while 48% offline is classified as low and the patient queue is only about 1 patient so there is no need for an additional registration server to speed up service. There was a difference between online and offline registration waiting times (p = 0.00) where online patients waited 4.91 minutes while offline patients waited 8.84 minutes. There is an effect of waiting time in the system on patient satisfaction (p = 0.00) so that to increase patient satisfaction, it is hoped that patients will register online.